Peningkatan Hasil Belajar Peserta Didik melalui Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Di SMP Negeri 1 Mahu - Dima, Siani Sintia; Bano, Vidriana Oktoviana; Enda, Riwa Rambu Hada (Jurnal Kridatama Sains dan Teknologi, 2023)
The background of this research is the low learning outcomes of class VII students of SMP Negeri 1 Mahu. The low learning outcomes can be influenced by the use of inappropriate learning models. This study aims to improve student learning outcomes through the application of a jigsaw cooperative learning model with a research approach using quantitative descriptive research on Environmental Pollution which includes understanding, characteristics, and ways to deal with pollution and environmental damage. This type of research is Classroom Action Research (CAR). Data collection techniques using tests and observations. The sampling technique uses a purposive sampling technique. Learning outcomes are focused on cognitive and affective domains. The results of this study indicate that the application of the jigsaw cooperative learning model can improve student learning outcomes. Learning outcomes in the cognitive domain increased by 30% and the affective domain by 23%. The conclusion is that the application of the jigsaw cooperative learning model can improve the learning outcomes of class VII students of SMP Negeri 1 Mahu on environmental pollution.Keywords: learning model, cooperative, jigsaw, learning outcomes